La metropoli dell’agente ich=Spaik: Libidissi di Georg Klein (Altre Modernità, 2014)
My paper focuses on Georg Klein’s Libidissi (1998) as an example of a new spy-story in contemporary German literature. Combining the analysis of the role of the German spy ich=Spaik, the main figure of Klein’s novel, with a mapping of the geographies of the city Libidissi, I will point out to what extent the author poses a challenge to the tradition of the spy-story and in what way he considers Ich=Spaik’s activities, intending them not only as an operation of espionage, but especially as a persistent questioning of a problematic identity, of a figure, who is continuously confronting the image of his native country, his original belonging with the Other. The representation of ich=Spaik’s ‘displaced’ identity and his approach to the landscape, the (in)visible town Libidissi, will be debated on two specific aspects: the paradigms of Self vs Other and of center vs periphery.